Analysis of Factors Influencing Fintech Service Adoption in Indonesia: A Study of DANA Digital Payment Service - Maharani, Adellia Rose Maya; Dias Satria (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the factors influencing the adoption of DANA fintech services in Indonesia. A quantitative approach was applied, using an online questionnaire distributed to 385 respondents. Generation Y and Z are used ase one of the criteria for the dominant group of digital service users. Data were analyzed using (SEM-PLS). The independent variables tested include perceived ease of use, perceived usefulness, attitude, financial literacy, user innovativeness, and government support. The results show that perceived ease of use, perceived usefulness, attitude, financial literacy, and user innovativeness have a significant effect on DANA adoption. Government support has no significant influence. These findings provide insights for fintech developers and policymakers to enhance digital financial service adoption more effectively.